2005
DOI: 10.1079/bjn20041383
|View full text |Cite
|
Sign up to set email alerts
|

Early enteral feeding compared with parenteral nutrition after oesophageal or oesophagogastric resection and reconstruction

Abstract: After resective and reconstructive surgery in the gastrointestinal tract, oral feeding is traditionally avoided in order to minimize strain to the anastomoses and to reduce the inherent risks of the postoperatively impaired gastrointestinal motility. However, studies have given evidence that the small bowel recovers its ability to absorb nutrients almost immediately following surgery, even in the absence of peristalsis, and that early enteral feeding would preserve both the integrity of gut mucosa and its immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 18 publications
0
90
1
5
Order By: Relevance
“…Shiraishi et al (2005) report no statistically significant difference in any outcomes between enteral and parenteral feeding groups, however, there were only 15 patients in this study. Gabor et al (2005) reported that patients in their combined group had a shorter stay on the intensive care unit and in the hospital overall, however, what is striking in this study is the extremely high anastomotic leak rate (48% for combined routes and 52% parenteral nutrition alone). The accepted anastomotic leak rate in oesophagectomy is less than 20,% (Briel et al 2004;Ercan et al, 2005;Law et al, 2005) raising concerns regarding the external validity of this study.…”
Section: Enteral Vs Parenteral Nutritioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Shiraishi et al (2005) report no statistically significant difference in any outcomes between enteral and parenteral feeding groups, however, there were only 15 patients in this study. Gabor et al (2005) reported that patients in their combined group had a shorter stay on the intensive care unit and in the hospital overall, however, what is striking in this study is the extremely high anastomotic leak rate (48% for combined routes and 52% parenteral nutrition alone). The accepted anastomotic leak rate in oesophagectomy is less than 20,% (Briel et al 2004;Ercan et al, 2005;Law et al, 2005) raising concerns regarding the external validity of this study.…”
Section: Enteral Vs Parenteral Nutritioncontrasting
confidence: 46%
“…Several studies have suggested that following gastrointestinal surgery, enteral nutrition is superior to parenteral nutrition (PN), resulting in a reduced length of hospitalisation and serious postoperative complication rates (McCarter et al, 1996;Velez et al, 1997;Aiko et al, 2001;Gabor et al, 2005;Mazaki and Ebisawa, 2008). However, these benefits are not necessarily reproduced following oesophagectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enteral nutrition is considered to be better than total parenteral nutrition for providing feeding in various clinical settings because it is less expensive, safer and maintains the nutritional, metabolic, immunological and barrier function of the intestines with fewer septic complications [6][7][8][9][10]. Jejunostomy is a surgical procedure by which a tube is situated in the lumen of proximal jejunum, primarily to administer enteral nutrition or sometimes medications and on rare occasion to aspirate intestinal contents.…”
Section: Introductionmentioning
confidence: 99%
“…In the remaining 14 (39%) patients a nasojejunal tube had to be placed because the jejunostomy had already been removed. Tube feeding was restarted via the jejunostomy at 34 days from surgery, and via the Duration within 6 months (days) 24 Continued tube feeding >6 months postoperative 9 [25] This table shows the data on restarting tube feeding within 6 months after discharge. Continuous variables data are presented as median [1st-3rd quartile], all other data are numbers [percentages].…”
Section: Days (Table 2)mentioning
confidence: 99%